Preparation method of high-valence Nb < 5 + > doped H2TiO3 lithium ion sieve

The preparation of H2TiO3 lithium ion sieve by using hollow anatase-type TiO2 and Nb5+ doping method was solved, and the problems of low adsorption capacity and high Ti4+ dissolution rate of existing titanium-based lithium ion sieve were solved, achieving efficient lithium ion adsorption and low dissolution rate, which was suitable for industrial production.

CN119549135APending Publication Date: 2025-03-04QINGHAI NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411954366.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The adsorption capacity of the existing titanium lithium ion sieve is not high, and the dissolution rate of Ti4+ is high, resulting in low lithium extraction efficiency and waste of resources.

Method used

Hollow anatase-type TiO2 is used as the titanium source, and Li2CO3 and Nb2O5 are added after ultrasonic dispersion, and a high-valent Nb5+ doped H2TiO3 lithium ion sieve was obtained through solid phase sintering and pickling ion exchange.

Benefits of technology

It significantly improves the adsorption capacity of Li+, reduces the dissolution rate of Ti4+, and has a simple process, which is suitable for large-scale production, providing more efficient lithium-ion sieves for lithium extraction in salt lakes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549135A_ABST
    Figure CN119549135A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-valence Nb < 5 + > doped H2TiO3 lithium ion sieve, and belongs to the technical field of preparation of inorganic materials. The method is simple and environment-friendly in process, free of organic matters and easy for large-scale production. The unique hollow structure and large specific surface area anatase type TiO2 are adopted as a titanium source, so that the specific surface area, porosity and particle dispersity of the H2TiO3 ion sieve are remarkably improved, adsorption active sites are increased, and the adsorption efficiency and capacity of lithium ions are improved; the structure of the lithium ion sieve is more stable by doping the titanium source with the hollow structure and Nb < 5 + >, and the dissolution loss rate of Ti < 4 + > is reduced. After multiple lithium ion adsorption / desorption cycles, the adsorption capacity of the lithium ion sieve is kept at a high level, and the dissolution loss rate of Ti < 4 + > is extremely low. The ion sieve has high adsorption efficiency, low solution loss rate and good cycle stability, is suitable for the fields of salt lake lithium extraction, lithium-containing wastewater treatment, lithium ion batteries and the like, can significantly improve the extraction efficiency and the battery performance, reduces resource waste and environmental pollution, reduces the production cost, and provides powerful support for technical progress and industrial development in related fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of inorganic materials, and in particular to a high-valent Nb 5+ Preparation method of doped H2TiO3 lithium ion sieve. Background Art

[0002] Lithium and its compounds have been widely used in many fields due to their excellent physical and chemical properties. The demand for lithium has increased rapidly in recent years. Especially in the context of "carbon peak" and "carbon neutrality", the use of rechargeable lithium-ion batteries (LIBs) in portable electronic products, large-scale grid energy storage and electric vehicles has increased, and the battery industry consumes the largest share of lithium resources in the world. In order to cope with and alleviate the potential risk of insufficient lithium resource supply in the future, the rational development and utilization of lithium is particularly important. At present, the lithium ion adsorbents commonly used for lithium extraction from salt lakes mainly include aluminum, antimony, manganese and titanium. Aluminum adsorbents have high selectivity and strong stability, but the adsorption capacity is not high. Although industrialized lithium extraction from salt lakes has been achieved, the efficiency is not high. Antimony adsorbents have high selectivity, large adsorption capacity and small dissolution loss, but antimonates are toxic and there are few related studies. Manganese lithium ion sieves, especially spinel manganese oxide lithium ion sieves, have many advantages, but the high Jahn-Teller effect and large manganese dissolution rate have always been two important defects in the lithium extraction process. Titanium-based lithium ion sieves are superior to manganese-based lithium ion sieves in terms of simple preparation, high selectivity, large adsorption capacity, and low dissolution loss rate. 12 There are two types of lithium ion sieves that can be used to extract lithium from weakly alkaline salt lakes. H4Ti5O 12 It is a spinel structure with the advantages of stable chemical structure and good cycle performance, but its adsorption capacity is not ideal. H2TiO3 with high adsorption capacity has a layered structure and high adsorption capacity, especially after activation and release, Li + The release rate can reach more than 98%, which is an adsorption material with broad industrial application prospects. However, in practical applications, H2TiO3 still has the problem that the adsorption capacity is difficult to reach the theoretical value, which is mainly attributed to its dense internal structure and narrow mass transfer channels, resulting in Li + The insertion and extraction of ions are hindered. In order to optimize the adsorption performance of titanium-based lithium ion sieves, ion doping modification is a common method. By changing the band gap structure of the material through doping and reducing particle agglomeration, the Li + Ion adsorption capacity.

[0003] Therefore, the key to improving the adsorption capacity of titanium-based lithium ion sieves is to improve the dispersion of material particles to reduce the agglomeration effect. Future research should focus on developing new dopants and modification methods to further improve the performance of titanium-based lithium ion sieves and meet the growing demand for lithium resources. At the same time, attention should also be paid to environmental protection and sustainability to ensure the rational development and utilization of lithium resources. Currently, the metals that are doped with more are all low-valent metal cations, and research on doping with high-valent metal cations has not been reported. Summary of the invention

[0004] Aiming at the ion agglomeration problem of the existing doped Hi2TiO3 ion sieve preparation method, Li + The adsorption capacity is not high, Ti 4+ The dissolution rate needs to be improved. The present invention aims to provide a high-valent Nb 5+ A method for preparing a doped H2TiO3 lithium ion sieve, wherein the method uses hollow anatase TiO2 as a titanium source, Nb 5+ Doping solid phase sintering not only solves the problem of H2TiO3 lithium ion sieve agglomeration caused by traditional high temperature calcination method, but also greatly improves Li + The adsorption capacity of Ti 4+ Dissolution loss provides strong support for the large-scale production of H2TiO3 lithium ion sieve.

[0005] The present invention solves the above technical problems through the following technical means:

[0006] The present invention provides a high-valent Nb 5+ The preparation method of the doped H2TiO3 lithium ion sieve is to use hollow anatase TiO2 as a titanium source, ultrasonically disperse, add Li2CO3 and Nb2O5, solid-phase sinter to obtain a Li2TiO3-Nb lithium ion sieve precursor, and then acid-wash the Li2TiO3-Nb lithium ion sieve precursor to obtain a high-valent Nb for lithium extraction from salt lakes. 5+ Doped H2TiO3 lithium ion sieve.

[0007] The preparation of the hollow anatase TiO2 comprises: dissolving anhydrous titanium sulfate and sodium fluoride, adding a nitrogen source for hydrothermal reaction, and filtering to obtain the hollow anatase TiO2, wherein the nitrogen source is any one of urea, ammonia water, nitrate and an organic nitrogen source.

[0008] Furthermore, the nitrogen source is urea.

[0009] The molar ratio of anhydrous titanium sulfate and sodium fluoride is 2-3:1, the added amount of the nitrogen source is 1-2:1 in mass ratio to the total amount of anhydrous titanium sulfate and sodium fluoride, the hydrothermal reaction temperature is 140-160° C., and the reaction time is 6-10 hours.

[0010] The mass ratio of the hollow anatase TiO2 and Li2CO3 is 1-2:1-2, and the added amount of Nb2O5 accounts for 2%-15% of the total mass of TiO2 and Li2CO3.

[0011] The dispersant is any one of anhydrous ethanol, acetone and isopropanol.

[0012] Furthermore, the dispersant is anhydrous ethanol.

[0013] The ultrasonic dispersion time is 40 min to 80 min, and the drying is performed at 60° C. to 80° C.

[0014] The solid phase sintering temperature is 700° C. to 800° C., and the heat preservation time is 4 h to 6 h.

[0015] The acid leaching uses any one of hydrochloric acid, sulfuric acid and nitric acid, and the acid leaching time is 20 to 26 hours.

[0016] The high-valent Nb obtained by the above preparation method 5+ H2TiO3 doped lithium ion sieve, the Nb 5+ Doped H2TiO3 lithium ion sieve ion adsorption / desorption cycle 5 times, adsorption capacity> 50mg / g, Ti 4+ The dissolution rate is less than 0.01%.

[0017] The above high-valent Nb 5+ Application of doped H2TiO3 lithium ion sieve in lithium extraction from salt lakes.

[0018] Compared with the prior art, the present invention achieves the following technical effects:

[0019] The high-valent Nb provided by the present invention 5+ The preparation method of doped H2TiO3 lithium ion sieve has a simple preparation process, does not use organic substances such as pore-forming agents and binders in the preparation process, is environmentally friendly and easy to mass produce; the method uses anatase-type TiO2 with a unique hollow structure and a large specific surface area as a titanium source, which significantly increases the specific surface area and porosity of the H2TiO3 lithium ion sieve, and has good particle dispersion and no obvious agglomeration, which is conducive to exposing more adsorption active sites, thereby further improving the adsorption efficiency and adsorption capacity of lithium ions; at the same time, the hollow structure titanium source and Nb 5+ High-valence doping can make the structure of H2TiO3 lithium ion sieve more stable and better able to resist Ti 4+ The dissolution of ions helps to reduce the dissolution rate of the adsorbent, thereby solving the ion agglomeration problem in the existing preparation method of high-valent ion-doped H2TiO3 lithium ion sieve, and also significantly improves the Li + The adsorption capacity of Ti 4+dissolution loss rate; through lithium ion adsorption / desorption cycle test, after multiple cycles, the adsorption capacity of lithium ion sieve still remains at a high level, and Ti 4+ The dissolution loss rate is extremely low, indicating the feasibility and effectiveness of the present invention in preparing high-performance and long-life titanium-based ion sieves, and providing strong support for the wide application of H2TiO3 ion sieves.

[0020] The high-valent Nb obtained by the preparation method of the present invention 5+ After five cycles of lithium ion adsorption / desorption, the adsorption capacity of the material still remained above 90% of the initial adsorption capacity, about 50 mg / g, which is significantly higher than the existing high-valent Nb 5+ Adsorption capacity of H2TiO3-doped lithium ion sieve; after 5 lithium ion adsorption / desorption cycles, Ti 4+ The dissolution rate is extremely low, less than 0.01%;

[0021] The high-valent Nb provided by the present invention 5+ Application of doped H2TiO3 lithium ion sieve in lithium extraction from salt lakes, the invention is used for high-valent Nb 5+ The doped H2TiO3 lithium ion sieve has a high specific surface area and porosity, as well as good particle dispersion, which can significantly improve the adsorption efficiency of lithium ions. In the process of lithium extraction from salt lakes, it can adsorb and enrich lithium ions faster, thereby improving the extraction efficiency. The stable lithium ion sieve structure of the present invention can better resist the dissolution of ions. In the process of lithium extraction from salt lakes, Ti 4+ The dissolution loss rate is extremely low, which helps to reduce resource waste and environmental pollution; the ion sieve has good cycle stability and can be used for lithium extraction from salt lakes for a long time, reducing production costs; the ion sieve of the present invention can not only be used to extract lithium ions, but also can be used to treat lithium-containing wastewater; in lithium-ion batteries, the ion sieve can be used as positive or negative electrode materials to improve battery performance and cycle stability; its broad application prospects provide strong support for technological progress and industrial development in related fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The scanning electron microscope image of the hollow anatase TiO2 raw material of the present invention; A is the electron microscope image at 10nm, and B is the electron microscope image at 1um;

[0023] Figure 2 This is a scanning electron microscope image of the lithium ion sieve prepared in Example 1 of the present invention; wherein A is an electron microscope image at 1 um, and B is an electron microscope image at 500 nm;

[0024] Figure 3 For the present invention, different Nb 5+ X-ray diffraction pattern of lithium ion sieve prepared by doping ratio;

[0025] Figure 4 This is a Fourier infrared spectrum of the lithium ion sieve prepared in Example 1 of the present invention;

[0026] Figure 5 This is an EDS-Mapping analysis diagram of the lithium ion sieve prepared in Example 1 of the present invention;

[0027] Figure 6 Cyclic adsorption / desorption of Li by the lithium ion sieve prepared in Example 1 of the present invention + Experimental comparison chart;

[0028] Figure 7 Cyclic adsorption / desorption of Li by the lithium ion sieve prepared in Example 1 of the present invention + Experimental adsorption capacity decay change diagram;

[0029] Figure 8 The high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ Adsorption capacity diagram of H2TiO3 lithium ion sieve doped with different ratios. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the experimental materials and reagents used in the following examples can be obtained from commercial sources.

[0032] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0033] Example 1

[0034] This embodiment provides a high-valent Nb 5+ The preparation method of doped H2TiO3 lithium ion sieve specifically comprises the following steps:

[0035] 1. Preparation of hollow anatase TiO2

[0036] Weigh 0.96 g (0.0076 mol) of anhydrous titanium sulfate and 0.15 g of sodium fluoride (0.0025 mol) and add them into a reactor containing 75 mL of secondary deionized water respectively, and stir magnetically to obtain a uniform solution; slowly add 1.92 g of urea (0.032 mol) and stir for 30 min. After removing the magnet, ultrasonicate at room temperature for 30 min. After hydrothermal treatment at 150 ° C for 8 h, filter and obtain hollow rutile TiO2.

[0037] 2. Preparation of high-valent Nb 5+ Doped H2TiO3 lithium ion sieve

[0038] 1.198 g of hollow TiO2 powder was weighed and dispersed in 50 mL of anhydrous ethanol. 1.108 g of Li2CO3 and 0.04 g of Nb2O5 powder were added and stirred for 3 h to obtain a mixture. The mixture was ultrasonically treated at room temperature for 60 min and dried at 60 °C. The dried mixture was placed in a muffle furnace and heated at 5 °C / min. -1 The temperature was raised to 750°C at a heating rate of 100 °C and kept for 5 h, then cooled to room temperature with the furnace, 200 mL of a hydrochloric acid solution with a molar concentration of 0.2 mol / L was added to 1 g of the precursor, and acid leaching was performed for 24 h to obtain the high-valent Nb 5+ Doped H2TiO3 lithium ion sieve (denoted as 2%-H2TiO3-Nb).

[0039] Example 2

[0040] This embodiment provides a high-valent Nb 5+ The preparation method of doped H2TiO3 lithium ion sieve specifically comprises the following steps:

[0041] 1.198 g of hollow TiO2 powder was weighed and dispersed in 50 mL of anhydrous ethanol. 1.108 g of Li2CO3 and 0.106 g of Nb2O5 powder were added and stirred for 3 h to obtain a mixture. The mixture was ultrasonicated at room temperature for 60 min and dried at 60 °C. The dried mixture was placed in a muffle furnace and heated at 5 °C / min. -1 The temperature was raised to 750°C at a heating rate of 100 °C and kept for 5 h, then cooled to room temperature with the furnace, 200 mL of a hydrochloric acid solution with a molar concentration of 0.2 mol / L was added to 1 g of the precursor, and acid leaching was performed for 24 h to obtain the high-valent Nb 5+ Doped H2TiO3 lithium ion sieve (denoted as 5%-H2TiO3-Nb).

[0042] Example 3

[0043] This embodiment provides a high-valent Nb 5+ The preparation method of doped H2TiO3 lithium ion sieve specifically comprises the following steps:

[0044] 1.198 g of hollow TiO2 powder was weighed and dispersed in 50 mL of anhydrous ethanol. 1.108 g of Li2CO3 and 0.199 g of Nb2O5 powder were added and stirred for 3 h to obtain a mixture. The mixture was ultrasonicated at room temperature for 60 min and dried at 60 °C. The dried mixture was placed in a muffle furnace and heated at 5 °C / min. -1 The temperature was raised to 750°C at a heating rate of 100 °C and kept for 5 h, then cooled to room temperature with the furnace, 200 mL of a hydrochloric acid solution with a molar concentration of 0.2 mol / L was added to 1 g of the precursor, and acid leaching was performed for 24 h to obtain the high-valent Nb 5+ Doped H2TiO3 lithium ion sieve (denoted as 10%-H2TiO3-Nb).

[0045] Example 4

[0046] This embodiment provides a high-valent Nb 5+ The preparation method of doped H2TiO3 lithium ion sieve specifically comprises the following steps:

[0047] 1.198 g of hollow TiO2 powder was weighed and dispersed in 50 mL of anhydrous ethanol, and 1.108 g of Li2CO3 and 0.299 g of Nb2O5 powder were added and stirred for 3 h to obtain a mixture. The mixture was ultrasonicated at room temperature for 60 min, dried at 60 °C, and the dried mixture was placed in a muffle furnace and heated at 5 °C / min. -1 The temperature was raised to 750°C at a heating rate of 100 °C and kept for 5 h, then cooled to room temperature with the furnace, 200 mL of a hydrochloric acid solution with a molar concentration of 0.2 mol / L was added to 1 g of the precursor, and acid leaching was performed for 24 h to obtain the high-valent Nb 5+ Doped H2TiO3 lithium ion sieve (denoted as 15%-H2TiO3-Nb).

[0048] Comparative Example 1

[0049] 1.198 g of hollow TiO2 powder was weighed and dispersed in 50 mL of anhydrous ethanol, and 1.108 g of Li2CO3 powder was added and stirred for 3 h to obtain a mixture. The mixture was ultrasonicated at room temperature for 60 min, dried at 60 °C, and the dried mixture was placed in a muffle furnace and heated at 5 °C / min. -1 The temperature was raised to 750°C at a heating rate of 100 °C and kept for 5 h, then cooled to room temperature with the furnace, 200 mL of a hydrochloric acid solution with a molar concentration of 0.2 mol / L was added to 1 g of the precursor, and acid leaching was performed for 24 h to obtain the high-valent Nb 5+ Doped H2TiO3 lithium ion sieve (denoted as: control H2TiO3).

[0050] Example 5

[0051] This example is based on Examples 1 to 4 to investigate the high-valent Nb obtained by the preparation method of the present invention. 5+ The performance of the H2TiO3 doped lithium ion sieve and the lithium ion sieve obtained in Comparative Example 1 is shown in the attached Figures 1 to 4 shown.

[0052] See attached Figure 1 , is a scanning electron microscope image of the hollow TiO2 in Example 1 of the present invention, Figure 1 It can be seen that the rutile TiO2 regulated by NaF has an obvious hollow structure, which helps to increase the specific surface area of ​​the material and provide more active sites for subsequent doping and ion sieve functionalization.

[0053] See attached Figure 2 , is the high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ SEM image of doped H2TiO3 lithium ion sieve (2%-H2TiO3-Nb), Figure 2 It can be seen that the high-valence Nb 5+ The doped H2TiO3 has excellent dispersibility, which significantly improves the particle agglomeration problem caused by high-temperature calcination. This improvement in dispersibility helps to increase the exposed crystal surface of H2TiO3 in the solution, thereby increasing the active sites and providing Li + It provides more adsorption sites and enhances the adsorption capacity of Li+.

[0054] See attached Figure 3 , which is the X-ray diffraction pattern of the lithium ion sieve obtained in Examples 1 to 4 of the present invention and Comparative Example 1, is shown in the attached Figure 3 The data show that the diffraction peaks of the precursor at 2θ=18.52°, 20.35°, 35.95°, 43.84°, 47.86°, 57.82°, 63.57° and 66.92° are attributed to the (002), (110), (131), (133) (204), (006), (206) and (062) crystal planes of monoclinic lithium metatitanate (JCPDS 33-0831), which is very consistent with the typical layered structure of Li2TiO3. There are no other impurity diffraction peaks in the diffraction spectrum, indicating that the product is of high purity. By comparison, it can be found that after Li2TiO3 is leached with hydrochloric acid, the diffraction peaks of the obtained H2TiO3 lithium ion sieve become weaker and wider, and move toward a larger 2θ angle. The disappearance of the (133) and (206) crystal planes is due to the smaller ionic radius of H2TiO3 in the Li2TiO3 crystal. + Replaced Li with a larger ionic radius +, resulting in the shrinkage of the unit cell and the broadening of the diffraction peak. In addition, the (002) and (131) crystal planes remain unchanged before and after acid leaching, indicating that the layered structure is not destroyed and the skeleton structure of Li2TiO3 still exists. A small amount of Nb 5+ Doping does not cause significant changes in the H2TiO3 lattice. 5+ When the doping amount reaches more than 2%, as Nb 5+ With the increase of doping amount, some main diffraction peaks such as (200) and (002) move toward the low angle direction of 2θ, accompanied by the weakening of diffraction peak intensity, indicating that the particle size of the sample is decreasing.

[0055] See attached Figure 4 , is the high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ Doped H2TiO3 lithium ion sieve and its Fourier infrared spectrum. Figure 4 The data show that at 3100-3500cm -1 The absorption peaks in the range can be attributed to the bending vibration of -OH, and Nb-HTO-2% is at 1631 cm -1 The absorption peak at 1440 cm-1 is attributed to the stretching vibration peak of -OH, indicating that the surface of the lithium ion sieve contains a large number of -OH hydrophilic groups. -1 There is an obvious absorption peak at the position, but the characteristic peak disappears after acid washing. + After 1507cm -1 This characteristic absorption peak was detected again at . This result is believed to be caused by the bending vibration of the Li-O bond in the material structure after adsorption, that is, the Li-O bond breaks after acid leaching to form HO bond, and the adsorbed Li + The Li-O bonds were then regenerated, which further confirmed the adsorption mechanism of lithium ion sieve.

[0056] See attached Figure 5 , is the high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ Doped H2TiO3 lithium ion sieve and its EDS-Mapping diagram, from the attached Figure 5 From the data, we can see that the Nb element is successfully doped into the H2TiO3 crystal structure and is distributed very evenly. The uniform doping distribution is of great significance for improving the structural stability and other properties of the material.

[0057] Example 6

[0058] This example is based on Examples 1 to 4 to investigate the high-valent Nb obtained by the preparation method of the present invention. 5+ The application of doped H2TiO3 lithium ion sieve, the specific steps are as follows:

[0059] (1) Adsorption test

[0060] In a strong alkaline solution of pH=13, weigh the high-valent Nb obtained by the preparation method of Example 1 of the present invention. 5+ 0.1 g of H2TiO3 lithium ion sieve was added to 50 mL of 0.1 mol / L LiCl solution and shaken at 25 °C and 150 rpm for 24 h. After the adsorption reached equilibrium, the supernatant was taken and the lithium ion concentration was measured by ICP-MS. The adsorption capacity of Nb-HTO-2% was calculated to be 48.6 mg g -1 .

[0061] (2) Adsorption / desorption test

[0062] The adsorption experiment was carried out according to step (1) in Example 6. When the adsorption reached equilibrium, the adsorption bottle was taken out from the constant temperature oscillator, and the powder after centrifugation was placed in a 60°C oven for drying. Then 1g of Nb-HTO-2%-Li was placed in 200mL 0.5mol / L HCl solution for acid leaching at room temperature for 4h, then centrifuged, washed with distilled water until neutral, and then placed in an oven for drying for the next cycle experiment. The adsorption cycle results are detailed in the attached Figure 6-7 As shown. Figure 6-7 The data show that after 5 adsorption / desorption experiments, Nb-HTO-2% has a strong affinity for Li + The adsorption capacity of MgO decreased from 58.1 mg / g to 46.1 mg / g. There are two main reasons for the decrease in adsorption capacity. One is that Li + With H + The exchange is incomplete, resulting in a reduction in the active sites of the material; secondly, the structure of the adsorbed material is damaged to a certain extent during the acid leaching process. 4+ The dissolution rate is less than 0.01%, indicating that acid leaching has no significant damage to the crystal structure of the adsorbent material. The above results show that Nb-HTO-2% lithium ion sieve has excellent structural stability and large adsorption capacity, and is expected to be used in industrial production.

[0063] See attached Figure 6 , is the high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ Ti of H2TiO3 doped lithium ion sieve after 5 cycles 4+ Dissolution diagram of Figure 6 The data show that, after high-valence Nb 5+ The doped H2TiO3 lithium ion sieve has excellent stability. After 5 cycles, Ti 4+ The dissolution loss does not exceed 0.01%, which further confirms the advantage of Nb-HTO-2% in structural stability.

[0064] See attached Figure 7, is the high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ The adsorption capacity of the doped H2TiO3 lithium ion sieve after 5 cycles of experiments. Figure 7 The data show that, after high-valence Nb 5+ The doped H2TiO3 lithium ion sieve has good cycle stability, and the adsorption capacity only drops from 58.1 mg / g to 46.1 mg / g, which indicates that Nb-HTO-2% has good cycle stability and reusability performance.

[0065] See attached Figure 8 , is the high-valent Nb obtained by the preparation method of Example 1 of the present invention 5+ Adsorption capacity diagram of H2TiO3 lithium ion sieve doped with different proportions. Figure 8 The data show that after 2% high-valence Nb 5+ The adsorption capacity of H2TiO3 lithium ion sieve is the highest. Figure 3 X-ray diffraction pattern of 2% high-valence Nb 5+ The crystallinity of H2TiO3 lithium ion sieve is the best, which further confirms that the 2% Nb 5+ It is the optimal doping ratio, which can maximize the adsorption performance of H2TiO3 lithium ion sieve.

[0066] In summary, the present invention uses hollow anatase TiO2 as a titanium source, adds Li2CO3 and Nb2O5 after ultrasonic dispersion, obtains a Li2TiO3-Nb lithium ion sieve precursor by solid phase sintering, and then obtains a Li2TiO3-Nb lithium ion sieve by acid washing and ion exchange. The process is simple, does not use organic substances such as pore-forming agents and binders, and is suitable for industrial production; the obtained high-valent Nb 5+ The doped H2TiO3 lithium ion sieve has excellent structural stability and large adsorption capacity, and is expected to be used in the industrial production of lithium extraction from salt lakes.

[0067] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A high-valent state of Nb 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: Using hollow structure anatase TiO2 as titanium source, adding Li2CO3 and Nb2O5, ultrasonic dispersion, solid phase sintering to obtain Li2TiO3-Nb lithium ion sieve precursor, and then acid washing and ion exchange of Li2TiO3-Nb lithium ion sieve precursor to obtain high-valent Nb for lithium extraction from salt lakes. 5+ Doped H2TiO3 lithium ion sieve.

2. A high-valent Nb according to claim 1 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The preparation of the hollow anatase TiO2 includes: dissolving anhydrous titanium sulfate and sodium fluoride, adding a nitrogen source for hydrothermal reaction, and filtering to obtain the hollow anatase TiO2, wherein the nitrogen source is any one of urea, ammonia water, nitrate and an organic nitrogen source.

3. A high-valent Nb according to claim 2 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The molar ratio of anhydrous titanium sulfate and sodium fluoride is 2-3:1, the added amount of the nitrogen source is 1-2:1 in mass ratio to the total amount of anhydrous titanium sulfate and sodium fluoride, the hydrothermal reaction temperature is 140-160° C., and the reaction time is 6-10 hours.

4. A high-valent Nb according to claim 1 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The mass ratio of the hollow anatase TiO2 and Li2CO3 is 1-2:1-2, and the added amount of Nb2O5 accounts for 2% to 15% of the total mass of TiO2 and Li2CO3.

5. A high-valent Nb according to claim 1 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The dispersant is any one of anhydrous ethanol, acetone and isopropanol.

6. A high-valent Nb according to claim 1 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The ultrasonic dispersion time is 40 min to 80 min, 60 o C~80 o C dry.

7. A high-valent Nb according to claim 1 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The solid phase sintering temperature is 700 o C~800 o C, the insulation time is 4 h to 6 h.

8. A high-valent Nb according to claim 1 5+ The preparation method of doped H2TiO3 lithium ion sieve is characterized in that: The acid used in the pickling is any one of hydrochloric acid, sulfuric acid and nitric acid, and the pickling time is 20 h to 26 h.

9. The high-valent Nb obtained by the preparation method according to any one of claims 1 to 8 5+ Doped H2TiO3 lithium ion sieve, characterized in that The Nb 5+ Doped H2TiO3 lithium ion sieve ion adsorption / desorption cycle 5 times, adsorption capacity> 50mg / g, Ti 4+ The dissolution rate is less than 0.01%.

10. The high-valent Nb according to claim 9 5+ Application of doped H2TiO3 lithium ion sieve in lithium extraction from salt lakes.

Citation Information

Cited By

  • High-hydrophilicity titanium-based lithium ion sieve based on synergistic surface and lattice regulation and preparation method of high-hydrophilicity titanium-based lithium ion sieve

    CN120841565A